Full-Scale Experimental Validation of Large-Eddy Simulation of Wind Flows over Complex Terrain: The Bolund Hill - Ashvinkumar Chaudhari; Antti Hellsten; Jari Hämäläinen (Advances in Meteorology)
Numerical simulation of local atmospheric flows around a complex topography is important for many wind energy applications, as it can help in locating and optimizing wind farms. The aim of this paper is to simulate the atmospheric flows over the challenging and complex site of Bolund Hill (in Denmark) using Large-Eddy Simulations (LES) and to validate the simulation methodology against full-scale measurements. Wind prediction over a potential inland wind park is the main application of the validated LES methodology. For the first time, LES-based results from more than one wind direction of the Bolund case are reported and analyzed in detail herein. The LES results from each direction are compared with the Bolund field data in a quantitative way, for example, by using simulation error. According to the results comparison, it is found that the LES model provides by far the most accurate prediction for turbulent kinetic energy. The simulation error of this LES model for predicting turbulent kinetic energy is 19% smaller than that of all other models, whether experimental or numerical, employed previously over Bolund Hill.